Preserving the scenic identity of the tangible and intangible heritage of puppet theater: conservation of content through forms (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The present work deals with the material conservation of the forms that give appearance to the puppets, as testimonies of the puppet theater as intangible heritage. These potentially contain the meaning and content of what is represented there. The alterations present in the materials of heritage pieces cause an aesthetic alteration, proportionally affecting their meaning. Advances in the detailed and individualized study adapted to concrete cases make it possible to identify and determine the possible causes and agents of deterioration that produce the damage and open new perspectives that allow the continuation and permanence of these artifacts. The way to perceive the narrative and comic content of these material artifacts depends on whether these pieces are dynamic and manipulable. The deactivation of these sculptural units can lead to the total and partial loss of the functionality and meaning of these plastic creations. This fact is a starting point for the implementation of preventive and curative conservation measures.
Keywords: puppet; cultural heritage; conservation; preventive conservation; restoration